An annotated synopsis of Leiothrix (Eriocaulaceae) with additional nomenclatural notes - Giulietti, Ana Maria (Phytotaxa, 2020)
Previous morphological and molecular studies indicate that the genus Leiothrix is a monophyletic and well supported clade in Eriocaulaceae. A taxonomic revision of the genus for the Flora Neotropica is in progress, but with the Flora do Brasil 2020 project now in its final stages, this synopsis became necessary to present an updated list of accepted species, their synonyms and typifications. Protologues and types of 122 previously published names have been reviewed. The genus now includes 39 species and six varieties, adding up to 42 taxa endemic to Brazil, occurring especially in the Espinhaço Range in Minas Gerais and Bahia States. One species extends from Brazil to other countries of northern South America and one species and one variety are found only in Venezuela. In this paper I propose 34 new synonyms, five new combinations, three changes of status, one neotype and 49 lectotypes.